PENANGANAN TINDAK PIDANA KORPORASI TERKAIT PERTANGGUNGJAWABAN TINDAK PIDANA KORUPSI OLEH PT NINDYA KARYA (PERSERO) DITINJAU DARI PERMA NOMOR 13 TAHUN 2016 - Indira Rawiyakhirty (Universitas Katolik Indonesia Atma Jaya, 2022)
Corporations as legal entities or subjects can give a major contribution in increasing economic growth and national development, but there are times when corporations commit various criminal acts (corporate crime) that have a detrimental impact on the state and society. In reality, corporations can be a place to hide assets resulting from criminal acts that are not touched by the legal process in criminal liability. The problem of corporate responsibility as a perpetrator of a crime is not a simple matter, considering that a corporation is a legal entity, not a person who can be subject to imprisonment. In addition, the problem also stems from the principle of no crime without error (geen straf zonder schold). Mistakes are known as mens rea or bad intentions that naturally only exist in natural people. Mens rea is an element that is difficult to prove from a corporation that is considered to have committed a crime, considering that corporations can only take action through the organ of board of directors. Corporations can be considered to have committed a crime based on the actions of the person who supervises the management of the corporation. On December 21, 2016, the Supreme Court stipulates Supreme Court Regulation Number 13 of 2016 concerning Procedures for Handling Criminal Cases by Corporations (Perma No. 13 of 2016). The existence of Perma Number 13 of 2016 has become the basis for law enforcement to be more confident in taking action against corporations that commit criminal acts. This study aims to find out how criminal responsibility can be charged to PT Nindya Karya (Persero) as a perpetrator of corruption and how to apply Perma Number 13 of 2016 in handling corruption cases committed by PT Nindya Karya (Persero). The method used is normative research. The criminal liability that can be imposed on PT Nindya Karya (Persero) is the principal crime in the form of a fine with a maximum provision plus 1/3 (one third). The determination of PT Nindya Karya (Persero) as a suspect in a criminal act of corruption is a concrete step in law enforcement in Indonesia in ensnaring corporations as perpetrators of criminal acts. This determination is a breakthrough in law enforcement, especially for the Corruption Eradication Commission (KPK) after the issuance of Perma No. 13/2016 which can be used as a guide in the implementation of handling corporate crimes.